2019
DOI: 10.1136/jnnp-2018-319831
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of fingolimod, dimethyl fumarate and teriflunomide for multiple sclerosis

Abstract: ObjectiveOral immunotherapies have become a standard treatment in relapsing-remitting multiple sclerosis. Direct comparison of their effect on relapse and disability is needed.MethodsWe identified all patients with relapsing-remitting multiple sclerosis treated with teriflunomide, dimethyl fumarate or fingolimod, with minimum 3-month treatment persistence and disability follow-up in the global MSBase cohort study. Patients were matched using propensity scores. Three pairwise analyses compared annualised relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 41 publications
6
57
0
1
Order By: Relevance
“…Comparable post-index ARR were observed between DMF and FTY, but were significantly lower with DMF versus TERI [16]. In contrast, Kalincik et al [17] showed a lower ARR on FTY compared with DMF and TERI analysing 614 (TERI), 782 (DMF) or 2332 (FTY) patients from the global MSBase cohort, staying at least 3 months on treatment. No differences in disability accumulation or improvement were found between these therapies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Comparable post-index ARR were observed between DMF and FTY, but were significantly lower with DMF versus TERI [16]. In contrast, Kalincik et al [17] showed a lower ARR on FTY compared with DMF and TERI analysing 614 (TERI), 782 (DMF) or 2332 (FTY) patients from the global MSBase cohort, staying at least 3 months on treatment. No differences in disability accumulation or improvement were found between these therapies.…”
Section: Discussionmentioning
confidence: 89%
“…The longer observation period on treatment (at least 24 months) produced more robust data especially in regards to disease progression and regression. patients Two previous studies also compared between these oral MS drugs [16,17]. Ontaneda et al, analysed patients from a commercial claims database, switching from platform disease-modifying therapies (DMTs) to DMF, FTY and TERI and staying on treatment for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study comparing three drugs: fingolimod, dimethyl fumarate, and teriflunomide, in 3728 adult patients demonstrated a lower annual relapse rate (ARR) in the fingolimod group, but no difference in accumulation or improvement in disability compared to other groups. Comparison between dimethyl fumarate and teriflunomide for same parameters indicated no difference either …”
Section: Multiphasic Diseasementioning
confidence: 87%
“…Comparison between dimethyl fumarate and teriflunomide for same parameters indicated no difference either. 13…”
Section: First-line Oral Medicationsmentioning
confidence: 99%